Guiding the selection of service identification methods based on SOA maturity level. Issue 3 (19th August 2019) - Bani-Ismail, Basel; Baghdadi, Youcef
Abstract : Purpose: A mature adoption of a service-oriented architecture (SOA) goes steadily through different levels of maturity, whereby each level has its own types of services (e.g. software services or business services). However, the identification of such services is not an easy task even though there exist many service identification methods (SIMs). This paper aims to propose a new approach to select SIMs. The proposed selection approach for SIMs uses the desired SOA maturity level as the main guidance to assist the organizations in selecting a suitable SIM for each level of SOA maturity. Design/methodology/approach: The methodology consists of three activities: surveying and selecting a suitable evaluation framework for SIMs, surveying and selecting a suitable SOA maturity model (SOAMM) and using the selected evaluation framework to decide a suitable SIM for the desired SOA maturity level with respect to the selected SOAMM. Findings: Welke's SOAMM and two existing evaluation frameworks for SIMs were found suitable to validate the proposed selection approach for SIMs. The two selected frameworks utilized the proposed selection approach to different degrees. To fully utilize the proposed selection approach, a comprehensive evaluation framework is required that addresses the most significant aspects of the existing SIMs. Originality/value: In this research, the authors propose a new way of using Welke's SOAMM to guide the organizations in selecting a suitable SIM from the existing evaluation frameworks for SIMs based on the desired SOA maturity level. In addition, the proposed selection approach improves the applicability of the existing evaluation frameworks, as it provides the organizations with a new way to select the methods.